Dismissal laws, innovation, and economic growth - Krishnamurthy V. Subramanian (Asian Development Bank Institute (ADBI), 2018)
I theoretically and empirically show that dismissal laws - laws that impose hurdles on firing of employees - spur innovation and thereby economic growth. Theoretically, dismissal laws make it costly for firms to arbitrarily discharge employees. This enables firms to commit to not punish short-run failures of employees. Because innovation is inherently risky and employment contracts are incomplete, dismissal laws enable such commitment. Specifically, absent such laws, firms cannot contractually commit so ex-ante. The commitment provided by dismissal laws encourages employees to exert greater effort in risky, but path-breaking, projects thereby fostering firm-level innovation. I provide empirical evidence supporting this thesis using the discontinuity provided by the passage of the federal Worker Adjustment and Retraining Notification Act. Using the fact that this Act only applied to firms with 100 or more employees, I undertake difference-in-difference and regression discontinuity tests to provide this evidence. Building on endogenous growth theory, which posits that economic growth stems from innovation, I also show that dismissal laws correlate positively with economic growth. However, other forms of labor laws correlate negatively with economic growth and swamp the positive effect of dismissal laws.
Keywords: F30; G31; J5; J8; K31; 330; Labor laws; R&D; Technological change; Law and finance; Entrepreneurship; Growth